Neighborhood-Level Poverty, Poverty-Associated Factors, and Severe Outcomes among Adults Hospitalized with Influenza—United States, 2012–2015. (4th October 2017) - Schicker, Rebekah Stewart; Yousey-Hindes, Kimberly; Rolfes, Melissa a; Cummings, Charisse Nitura; Anderson, Evan J; Bargsten, Marisa; Bennett, Nancy; Eckel, Seth; Lung, Krista; McMahon, Melissa; Miller, Lisa; Monroe, Maya; et al.
Abstract: Background: Recent studies demonstrated higher influenza-associated hospitalization rates among individuals living in high-poverty neighborhoods. We explored the further impact of neighborhood-level poverty and individual, poverty-associated factors, on severe outcomes among hospitalized patients with influenza. Methods: We linked 2012–2015 data on hospitalized adults from the influenza hospitalization surveillance network (FluSurv-NET), by census tract, to the American Community Survey's federal poverty estimates. High-poverty neighborhoods were defined as census tracts with ≥20% of households in poverty and low-poverty neighborhoods, <5%. We explored univariate associations between neighborhood-level poverty and influenza vaccination, tobacco use, alcohol abuse, and extreme obesity. Using logistic regression and clustering by census tract, we examined the independent association of these factors with intensive care unit (ICU) admission and death, controlling for age, race, sex, comorbid conditions, antiviral treatment, season, and time from symptom onset to hospitalization. Results: Among 26, 106 patients, 4, 194 (16%) required ICU admission and 669 (3%) died. Those who currently used tobacco, abused alcohol, were extremely obese, or were unvaccinated were more likely to live in high-poverty (38%, 40%, 37%, 33%) compared with low-poverty neighborhoods (12%, 13%, 13%, 16%; P < .01), respectively. Living in a high-poverty neighborhood was not independently associated with ICU admission (OR: 0.97, CI: 0.87–1.10) or death (OR: 0.82, CI: 0.63–1.08). Being unvaccinated (OR: 1.24, CI: 1.15–1.35), tobacco use (OR: 1.31, CI: 1.19–1.45), and alcohol abuse (OR: 1.68, CI: 1.41–2.00) increased odds of ICU admission; extreme obesity increased odds of death (OR: 1.35, CI: 1.02–1.78). Conclusion: Poverty-associated factors, but not neighborhood-level poverty, were independently associated with severe outcomes among patients hospitalized with influenza. Increased vaccination and reductions in tobacco use, alcohol abuse, and extreme obesity could reduce severe influenza-associated outcomes. Disclosures: E. J. Anderson, AbbVie: Consultant, Consulting fee; NovaVax: Research Contractor, Research support; Regeneron: Research Contractor, Research grant; MedImmune: Research Contractor, Research grant and Research support; W. Schaffner, Pfizer: Scientific Advisor, Consulting fee; Merck: Scientific Advisor, Consulting fee; Novavax: Consultant, Consulting fee; Dynavax: Consultant, Consulting fee; Sanofi-pasteur: Consultant, Consulting fee; GSK: Consultant, Consulting fee; Seqirus: Consultant, Consulting fee